Comparison of ultrasound-guided endovenous laser ablation and radiofrequency for the varicose veins treatment: An updated meta-analysis. (March 2017) - He, Guangzhi; Zheng, Chenhong; Yu, Ming-An; Zhang, Hongpeng
Abstract: Purpose: To investigate and compare the relative efficacy, recurrence and complications of endovenous laser ablation (EVLA) and radiofrequency ablation (RFA) for the treatment of varicose veins patients. Methods: Searches were applied to the Cochrane Library as well as MEDLINE, EMBASE, BIOSIS databases. 12 articles published in English (10 randomized controlled trials and 2 cohort study) were identified from specialized trails. Fixed effect model and Random effect model were applied to compare the vein ablated length, pain scores (3days and 10days), quality of Life, occlusion, over all complication, thrombophlebitis, haematoma and recanalization between the EVLA and RFA group. The results were expressed as odds ratio (OR) or relative risk (RR) and 95% confidence intervals (CI) for categorical outcomes. Results: 12 reported studies with a combined total of 1577 patients were included. vein ablated length (SMD:0.37, 95%CI: 0.04 to 0.77), 3days pain scores (SMD:11.25, 95%CI: 3.42 to 25.92) and 10days (SMD:0.79, 95%CI: 0.48 to 2.05), 1 month quality of Life (SMD: 0.09, 95%CI: 0.28 to 0.10) and 1 year (SMD: 0.04, 95%CI: 0.21 to 0.13), occlusion (OR:1.05, 95%CI:0.41 to 2.73), thrombophlebitis (RR:1.03, 95%CI:0.56 to 1.92), haematoma (OR:1.55, 95%CI:0.54 to 4.45) and recanalization (OR:0.68, 95%CI:0.43 to 1.09) following RFA showed no difference when compared with EVLA. These results were not statistically significant. RFA was associated with the lower overall complication (OR: 3.49, 95%CI:1.36 to 8.96) in patients with varicose veins compared to the EVLA treatment. Conclusion: EVLA and RFA seem to be the same safe and effective on clinical efficacy (vein ablated length, 3days and 10days pain scores, 1 month and 1 year quality of life, occlusion, thrombophlebitis, haematoma and recanalization). Data on RFA seems to having potential benefits from reducing risk of overall complication than EVLA, which is needed by large high-quality prospective randomized trials. Highlights: EVLA and RFA has the same safety and efficacy (including vein ablated length, 3days and 10days pain scores, 1 month and 1 year quality of life, occlusion, thrombophlebitis, haematoma and recanalization). Twelve studies included 1577 patients for treatments: 792 for EVLA and 785 for RFA. Interestingly, RFA seems to having benefits with lower risk of overall complication than EVLA.